Small Volume Plasma Exchange as an Alternative to Conventional Plasma Exchange and Intravenous Immunoglobulin for Myasthenic Crisis: A Case Report - Rimal, Ankit; Shrestha, Gentle Sunder; Pradhan, Bishwas; Acharya, Subhash Prasad (Journal of Advances in Internal Medicine, 2023)
Myasthenic crisis is a life-threatening condition. At times it manifests as the initial presentation of the underlying myasthenia gravis. Rapidly acting therapies for treatment of this condition are plasma exchange and intravenous immunoglobulin. We report a case of myasthenic crisis in a young female, presenting with respiratory failure and bulbar symptoms. She had significantly raised titres of anti-acetylcholine receptor antibody. She was treated with multiple sessions of small volume plasma exchange. This modification of conventional plasma exchange significantly reduces costs and is potentially an effective alternative to conventional plasma exchange and intravenous immunoglobulin in resource-poor settings.